A structural equation model of tourism activities, social interaction and the impact of tourism on youth tourists' QOL. (2016) - Eusébio, Celeste; Carneiro, Maria João; Caldeira, Ana
The current study aims to develop a model in the scope of youth tourism that illustrates structural relationships among the following constructs: 1) frequency of participation in several tourism activities; 2) frequency of social interaction with residents; 3) perception of tourism impacts on several domains of quality of life (QOL); 4) perception of tourism impacts on overall QOL. To achieve this objective, a survey was carried out with university students and 412 completed questionnaires were obtained. The model was tested with partial least squares structural equation modelling (PLS-SEM). Results show a strong positive impact of tourism activities on social interaction and a positive impact of both tourism activities and social interaction on all domains of QOL - physical health, social relationships, psychological features and environmental conditions. The paper ends with recommendations for improving the impact of tourism on youth visitors' QOL.